Scenarios for Global Aquaculture and Its Role in Human Nutrition. Issue 1 (3rd August 2020) - Gephart, Jessica A.; Golden, Christopher D.; Asche, Frank; Belton, Ben; Brugere, Cecile; Froehlich, Halley E.; Fry, Jillian P.; Halpern, Benjamin S.; Hicks, Christina C.; Jones, Robert C.; Klinger, Dane H.; Little, David C.; et al.
Abstract: Global demand for freshwater and marine foods (i.e., seafood) is rising and an increasing proportion is farmed. Aquaculture encompasses a range of species and cultivation methods, resulting in diverse social, economic, nutritional, and environmental outcomes. As a result, how aquaculture develops will influence human wellbeing and environmental health outcomes. Recognition of this has spurred a push for nutrition-sensitive aquaculture, which aims to benefit public health through the production of diverse, nutrient-rich seafood and enabling equitable access. This article explores plausible aquaculture futures and their role in nutrition security using a qualitative scenario approach. Two dimensions of economic development – the degree of globalization and the predominant economic development philosophy – bound four scenarios representing systems that are either localized or globalized, and orientated toward maximizing sectoral economic growth or to meeting environmental and equity dimensions of sustainability. The potential contribution of aquaculture in improving nutrition security is then evaluated within each scenario. While aquaculture could be "nutrition-sensitive" under any of the scenarios, its contribution to addressing health inequities is more likely in the economic and political context of a more globally harmonized trade environment and where economic policies are oriented toward social equity and environmental sustainability.